Analysis of Financial Performance towards Islamic Cooperatives Using DuPont System and Sharia Conformity and Profitability Techniques in Pontianak City for the 2014-2017 Periods - Lestari, Isna Ayu; Anwari, Khoirul; Rasiam, Rasiam (Khatulistiwa, 2020)
Assessing financial performance is needed for companies in order to know the overview of financial condition which reflects work performance in a certain period. Thus, financial performance assessment with DuPont System and Sharia Conformity and Profitability techniques is a technique of assessing financial performance not only from financial performance itself but also the level of sharia compliance towards the sharia cooperative. This research aims to find out: (1) Financial performance of Islamic cooperatives in Pontianak City in the 2014-2017 period based on DuPont System analysis, (2) the performance of sharia compliance of Islamic cooperatives in Pontianak City in the 2014-2017 period using the Shariah Conformity and Profitability (SCnP) Model. The method employed is quantitative with a descriptive approach. Data collection technique used was the documentation technique which is a financial report. The result of this study is different during periods among sharia cooperatives which have good financial performance as well as good sharia compliance and vice versa, some have good financial performance but sharia compliance is not well perform and vice versa.